Nursing care in improving the quality of life of chronic kidney disease patients (Research, Society and Development, 2025)
Chronic Kidney Disease (CKD) is a slow and progressive decline in the exocrine and endocrine functions of the kidneys. CKD generates numerous negative repercussions on the physical and biopsychosocial aspects of the individual, thereby affecting and compromising quality of life. The objective of this study was to identify the role of nursing care in improving the quality of life of patients with chronic kidney disease. This study was conducted through a narrative literature review. Twenty articles from the past five years were included for the development of this paper, and five were excluded. The findings showed that the nursing team is responsible for providing care related to personal health management, making the patient an active participant in the health-disease process and contributing to an improvement in the quality of life of patients with CKD. Therefore, aligned with quality of life, nursing care is essential for the recovery of these patients, consequently improving lifestyle habits and minimizing comorbidity rates.